Anatomia Foliar de Microlicia D. Don - Freitas, Lígia Silva (2015)
Melastomataceae Juss, the largest family of the order Myrtales, is widely distributed pantropical. The family is one of the largest of the Brazilian flora, with about 150 genera and 4,500 species. Melastomataceae is divided into 11 tribes, with Melastomeae Bartl., Miconieae DC. and Microlicieae Naudin the most important tribes in Brazil, and in Brazil can be found about 1/3 of its species. Microlicia D. Don the largest genus of Microliciae tribe and one of the most representative genera, with about 120 species, mainly concentrated to the “campos rupestres” in the Central Brazil. Although Microlicia reaching its greatest diversity in the Brazilian “campos rupestres”, some species are widely distributed and can be found in other vegetation types such as cerrado, paths, swamps and hydromorphic fields. Microlicia is considered a problematic genus among the Melastomataceae, and their species are recognized only by combining different traits, making it difficult to accurately identify several of them. In an attempt to help the delimitation of the most problematic species, in the last decade a great effort has been devoted to the study of Microlicia leaf anatomy and today around 1/3 of these species have had the leaf anatomy described. The most common features are: unisseriate epidermis, amphistomatic leaves, presence of trichomes and emergences, isobilateral or homogeneous mesophyll and presence of phenolic compounds in leaf tissues, particularly in the palisade parenchyma cells. However, despite the many similar features, Microlicia leaves also exhibit different anatomical characteristics that could help identify the most problematic species. Considering the large number of Microlicia species with the leaf anatomy known, the polymorphism already reported for several species of the genus, and the possible plastic potential of the leaf anatomy that the species of widely spread could present, the goals of this work were: a) analyze the leaf anatomy of nine Microlicia from “campos rupestres”; b) analyze and interpret the leaf anatomy of four species occurring in others environments, beyond the “campos rupestres” and c) through similarity analysis performed using the anatomical leaf traits of the all Microlia studied to date, analyze the groups of similar species formed and identify characters that favor the formation of the same.